PERKUATAN ( STRENGTHENING) STRUKTUR BETON DENGAN FIBER REINFORCED POLYMER (FRP) - Christiawan, Ignatius (METANA, 2009)
Abstract Â  In effort fulfill requirement the well building infrastructure, safety of building user such as building avalanche damage as result of earthquake is principal priority. Load addition on building exceeds the planning load as result of the involuntary building function change always generating the building avalanche damage. It was needed evaluate to the strength of building structure at the existing condition and strengthening if it was needed before the structure given the new load. One of the strength procedure is external reinforcement method especially give Fiber Reinforced Polymer (FRP) that it was adhered on the concrete component surface which reinforced by epoxy glue. From several former researches, base analysis and bent planning along with example of the practice calculation of beam strength by FRP can be concluded that the use of FRP in combination with the others strength method is easy and practice for conducted and also capable to increase the strength of concrete beam bent. Â  Kcywords: load addition, strength, safety